The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph182212046
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiles of Leaves and Roots of Goldenrain Tree (Koelreuteria paniculata Laxm.) in Response to Cadmium Stress

Abstract: Cadmium (Cd) pollution is a widespread environmental problem. In this study, we explored the transcriptome and biochemical responses of goldenrain tree (Koelreuteria paniculata Laxm.) leaves and roots to Cd stress. Leaf and root growth decreased substantially under Cd stress (50 mg/L CdCl2), but leaf and root antioxidant mechanisms were significantly activated. In RNA-seq analysis, roots treated with 25 mg/L CdCl2 featured enriched GO terms in cellular components related to intracellular ribonucleoprotein comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…A growing body of research indicates that TFs are important regulators of the plant response to abiotic stress. In particular, the WRKY, MYB, bHLH, ERF, ZIP, and C2H2 TFs have been implicated in the Cd stress response (Tokumoto et al, 2019;He et al, 2021). We found that the ERF, MYB, C2H2, NAC, WRKY, and G2-like TFs were highly responsive to Cd in the roots and aerial tissues of both uninoculated and "CD2"-inoculated plants (Figure 6), suggesting that these TFs represent an innate Cd stress-resistance mechanism in B. rapa.…”
Section: Discussionmentioning
confidence: 83%
“…A growing body of research indicates that TFs are important regulators of the plant response to abiotic stress. In particular, the WRKY, MYB, bHLH, ERF, ZIP, and C2H2 TFs have been implicated in the Cd stress response (Tokumoto et al, 2019;He et al, 2021). We found that the ERF, MYB, C2H2, NAC, WRKY, and G2-like TFs were highly responsive to Cd in the roots and aerial tissues of both uninoculated and "CD2"-inoculated plants (Figure 6), suggesting that these TFs represent an innate Cd stress-resistance mechanism in B. rapa.…”
Section: Discussionmentioning
confidence: 83%
“…These ndings highlight the MTP genes' interspeci c functional variety and spatial expression in HM stress responses. Numerous transcriptome studies on HM stress have shown this behavior 40,41 .…”
Section: The Seven-branch Model May Elucidatebjmtpfunctional Diversitymentioning
confidence: 96%
“…Arabidopsis thaliana plants overexpressing tomato metallocarboxypeptidase inhibitor (TCMP-1) displayed a lower amount of Cd accumulation in shoots and an increased expression of heavy metal-associated isoprenylated plant protein (AtHIPP26) in comparison with wild-type plants (Manara et al 2020). Few researchers indicated that different transcription factors, including C2H2, MYB, WRKY, and bZIP family members, respond to Cd stress (He et al 2021). Moreover, two basic helix-loop-helix (bHLH) transcription factors (bHLH29 and bHLH38) were different between two wheat genotypes with contrasting Cd accumulation (Sabella et al 2021).…”
Section: Introductionmentioning
confidence: 99%